'No So Komo Las De Agora' (I'm not like those modern girls): Judeo-Spanish Songs Meet the Twenty-First Century - Cohen, Judith R. (European Judaism, 2011)
The Judeo-Spanish song tradition has experienced many changes in recent years as it enters the 'world music' scene. Change, however, can be seen as a constant feature of the many aspects of Judeo-Spanish song and performance practice. Here, various genres are examined, together with some of the changes they have undergone in repertoire, style and context, and a selection of reactions to changes on the part of Sephardi Jews interviewed over several years. To a large extent, the repertoire has moved from the home to public representation, and is performed more by professional artists with no Sephardi background than by people from Sephardi communities, raising questions of appropriation and representation.

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

Musical Life in Montreal's Judeo-Spanish Community - Cohen, Judith R. (Garland Encyclopedia of World Music, tome III : United States and Canada, 2001)

The Role of Music in the Quebec Sephardic Community - Cohen, Judith R. (Contemporary Sephardic Identity in the Americas: An Interdisciplinary Approach, 2012)

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)